1995
DOI: 10.1002/mrd.1080410304
|View full text |Cite
|
Sign up to set email alerts
|

Sry‐negative XX sex reversal in the American cocker spaniel dog

Abstract: The Sry gene product serves an important function in male sex determination through testis induction. However, testicular development has been reported in SRY-negative XX sex reversed humans. XX sex reversal of the American cocker spaniel, inherited as an autosomal recessive trait, may be a homolog of this disorder. The purpose of this study was to determine whether the Sry high mobility group (HMG) box is present in genomic DNA of affected dogs. Conserved Sry HMG box and hypoxanthine phosphoribosyltransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 29 publications
(55 reference statements)
1
30
0
Order By: Relevance
“…Coyote-derived faeces were sexed based on the presence of PCR product from the Y-chromosome SRY gene (Meyers-Wallen et al 1995). PCR of mtDNA and SRY used 50 ng of DNA isolated from blood or 5 ml of DNA extracted from faeces in a 20 ml reaction volume containing 1.0 mM MgCl 2 , 1.0 mg ml À1 bovine serum albumin (BSA), 0.05 mM of each dNTP, 5.0 pmoles of each primer, 1 ÂPCR reaction bu¡er and 0.3 units of Taq.…”
Section: (C) Faecal Typingmentioning
confidence: 99%
“…Coyote-derived faeces were sexed based on the presence of PCR product from the Y-chromosome SRY gene (Meyers-Wallen et al 1995). PCR of mtDNA and SRY used 50 ng of DNA isolated from blood or 5 ml of DNA extracted from faeces in a 20 ml reaction volume containing 1.0 mM MgCl 2 , 1.0 mg ml À1 bovine serum albumin (BSA), 0.05 mM of each dNTP, 5.0 pmoles of each primer, 1 ÂPCR reaction bu¡er and 0.3 units of Taq.…”
Section: (C) Faecal Typingmentioning
confidence: 99%
“…, Teppei KANDA 1) , Masashi NAGANO 2) , Akihiko SUGIYAMA 3) , Yoshiharu OKAMOTO 4) and Yoshiaki HIKASA 5) 1) Departments of Veterinary Internal Medicine, 2) Theriogenology, 3) Laboratory Medicine, 4) Veterinary Neurology and Oncology and 5) Veterinary ABSTRACT. A 10-year-old Miniature Schnauzer with bilateral cryptorchidism and male external genitalia was referred with a history of abdominal enlargement.…”
mentioning
confidence: 99%
“…To investigate the karyotype of the dog, chromosome preparations were obtained from a peripheral blood lymphocyte culture and stained with Giemsa [4]. Cytogenetic evaluation revealed a normal male chromosome compliment, 78, XY.…”
mentioning
confidence: 99%
“…In a previous report by Meyers-Wallen et (1999) a similar case was described but karyotypic confirmation of sex chromosomes was lacking. A retrospective study described a similar case (Meyers-Wallen et al 1995b), which indicated that three American Spaniel dogs had testicular tissue on the basis of gonadal histology but were negative for the presence of Sry based on PCR assays of genomic DNA. Although a large number of important genes are considered to be involved in testis differentiation, the genetic aetiology of SRY-negative XXSR in mammals is unexplained.…”
Section: Discussionmentioning
confidence: 99%